Papel da cultura organizacional no desenvolvimento do método Customer Success em uma grande empresa de tecnologia do mercado financeiro - Fonseca, Júlia Valério da (Universidade Federal de São Carlos, 2023)
Customer Success has been increasingly sought after by companies, it focuses on promoting customer success through a better understanding of their needs and greater engagement with the service flow. CS can influence better profit predictability, greater customer retention, increased loyalty, among other aspects that can have a positive impact on the results of the company that employs it and what can influence the performance of this method is the organizational culture. This study aims, through a case study with participant observation and interviews with all workers in the CS area of a large technology company in the financial market, to analyze how the characteristics of the organizational culture identified in the company influence the development of the area of Customer Success. From this study, it was found that culture has a significant impact on the development of the area by disseminating values and objectives to people and strategic areas, engaging the company as an aggregator and alignment instrument between areas, influencing the feeling and collaboration between employees, direct how the company should act to achieve its goals, among other factors.
Role of organizational culture in the development of Customer Success method in a large technology company in the financial market
Keywords: Customer Success; Organizational Culture; Financial Market; Cultura Organizacional; Experiência do Cliente; Mercado Financeiro; ENGENHARIAS::ENGENHARIA DE PRODUCAO